PERAN BRAND IMAGE MEMEDIASI PENGARUH E-WOM TERHADAP NIAT BELI SMARTPHONE VIVO DI KOTA DENPASAR - Andreana, Kadek Agus Yoga; Giantari, I Gusti Ayu Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023DO - 10.24843/EEB.2023.v12.i06.p06, 2023)
The phenomenon of smartphones becoming secondary goods makes people's demand for smartphones increase , so that Vivo as one of the smartphone vendors in Indonesia, needs to carry out the right strategy to increase people's purchase intentions for their smartphones. The purpose of this study was to explain the role of brand image in mediating the effect of E-WOM on Vivo smartphone purchase intentions in Denpasar City. The sample used in this study was 100 respondents using a questionnaire tool. The sample was determined using non-probability sampling model with purposive sampling technique. The data analysis technique used is path analysis with the help of SPSS program. The results show that E-WOM has a positive and significant effect on purchase intention, E-WOM has a positive and significant effect on brand image, brand image has a positive effect on purchase intention, brand image is able to mediate the effect of E-WOM on purchase intention. This research implication is that Vivo need to maintain and pay attention to their strategies to make e-wom and brand images better to increase purchase intentions.